The "C" word and the third sector a case study of Transparency International Czech Republic - Lance, Anne C. (2006)
This paper examines the global phenomenon of corruption and the role NGOs play in the anticorruption fight. Definitions of corruption are explored and a small section explores the prevalence of corruption in post communist countries. The phenomenon of the global "corruption eruption" is explored in terms of the end of the Cold War, the spread of democracy, US global business interests, and the changing role of Bretton Woods institutions. A brief chapter examines the role NGOs play in international politics and then the paper moves to its discussion of the origins, strategies, and tools Transparency International uses in its fight against corruption. Finally, the remainder of the paper explores, in depth, the inner workings of Transparency International Czech Republic and its contribution to the Czech anticorruption fight; evaluating its strategies, projects, and successes as a political actor in the Czech political sphere.